PENGARUH Brand Ambassador dan Citra Merk terhadap Keputusan Pembelian Sepeda Motor Suzuki Type Nex - Gigih Wahyu Utomo; Bulan Prabawani (Universitas Diponegoro, 2017)
This research is motivated by business competition in the current era of globalization more dynamic and complex, the existence of this competition not only raises opportunities but also poses a challenge. The challenges faced by competing companies are always trying to find the best way to seize and maintain market share. The company must be able to determine the right marketing strategy so that its business can survive and win the competition, so that the purpose of the company can be achieved. The first hypothesis that there is an influence between brand ambassador and customer purchase decisions has been proven. This is proven through research with the results of calculating the value of t arithmetic of 11.113 which is greater than t table 1.6772 which indicates that brand ambassador has a significant relationship to the purchase decision. So the one hypothesis that reads